Revealing the Concealed in Monocular and Binocular Vision - Nicholas J. Wade (Vision)
Concealing images has been a concern of artists and scientists, as have the conditions that can reveal them. It is relatively easy to hide images in pictures, but this is of little value if they remain hidden. The skill is in revealing previously concealed images. Three aspects of hiding images are examined, two of which are monocular and the third is binocular. Firstly, high-contrast patterns, like Street figures and Mooney faces, have been used in psychological tests of pattern recognition, and Gestalt grouping principles can result in concealing images. Second, it is possible to hide low spatial frequency content carried by high-spatial-frequency patterns. A wider range of carriers than gratings can be used, like graphics, photographs, and combinations of them (photo-graphics). Pictorial images can be concealed in terms of detection or recognition. In both cases, there is interplay between the global features of the concealed image and the local elements that carry it. Third, randomly textured stereograms reveal to two eyes what is concealed from each one alone—stereoscopic depth. The dimension of stereoscopic depth can be manipulated, as can that of binocular rivalry, to conceal images.